2021
DOI: 10.1101/2021.12.01.470789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic architecture drives population structuring in Amazonian birds

Abstract: Large rivers are ubiquitously invoked to explain the distributional limits and speciation of the Amazon Basin’s mega-diversity. However, inferences on the spatial and temporal origins of Amazonian species have narrowly focused on evolutionary neutral models, ignoring the potential role of natural selection and intrinsic genomic processes known to produce heterogeneity in differentiation across the genome. To test how these factors may influence evolutionary inferences across multiple taxa, we sequenced whole g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 159 publications
(293 reference statements)
0
5
0
Order By: Relevance
“…We may expect increased diversity in high recombination regions due to decreased effects of linked selection and genetic drift as well as a higher propensity for gene flow. This positive association between genetic diversity and recombination rate has been observed in multiple species of animals, fungi, and plants (Branca, et al 2011;Payseur 2013, 2003;Dutoit, et al 2017b;Kraft, et al 1998;Kulathinal, et al 2008;Moreira, et al 2022;Roesti, et al 2013;Takahashi, et al 2004;Thom, et al 2021;Vijay, et al 2016;Vijay, et al 2017).…”
Section: Genomic Architecture Shapes Genomic Diversity Divergence And...mentioning
confidence: 71%
See 1 more Smart Citation
“…We may expect increased diversity in high recombination regions due to decreased effects of linked selection and genetic drift as well as a higher propensity for gene flow. This positive association between genetic diversity and recombination rate has been observed in multiple species of animals, fungi, and plants (Branca, et al 2011;Payseur 2013, 2003;Dutoit, et al 2017b;Kraft, et al 1998;Kulathinal, et al 2008;Moreira, et al 2022;Roesti, et al 2013;Takahashi, et al 2004;Thom, et al 2021;Vijay, et al 2016;Vijay, et al 2017).…”
Section: Genomic Architecture Shapes Genomic Diversity Divergence And...mentioning
confidence: 71%
“…Previous work in insects, birds, and mammals has shown that phylogenomic signal varies across the genome (Edelman, et al 2019;Fontaine, et al 2015;Martin, et al 2019;Thom, et al 2021). Generally, these studies have found or suggested that the background species tree is best represented by phylogenomic patterns exhibited in genomic regions with low recombination, and that gene flow among taxa is more prevalent in genomic regions with high recombination rate (Edelman, et al 2019;Martin, et al 2019;Thom, et al 2021). Our results in the Brown Creeper echo these findings, whereby we find highest support for the genome-wide supported phylogenomic relationships in genomic regions with low recombination rate (Fig.…”
Section: Phylogeographic Structure Shaped By Genomic Architecturementioning
confidence: 99%
“…Amazonian biogeography has been at the center of discussions on how landscape evolution leads to allopatric speciation (Haffer 1997;Ribas et al 2012), but increasingly, researchers are discovering that the histories of taxa across this landscape are marked by high gene flow (Barrera-Guzmán et al 2022). Recent genomic studies have reported introgression across rivers and considerable phylogenetic conflict, often despite strong genetic and phenotypic structuring (Thom et al 2021;Del-Rio et al 2022;Musher et al 2022). This includes examples of hybrid speciation (Barrera-Guzmán et al 2018), mitonuclear discordance (Del-Rio et al…”
Section: Biogeographic and Geogenomic Implicationsmentioning
confidence: 99%
“…In contrast to intrinsic genomic architecture, biogeographic history is an important extrinsic factor influencing reticulation and the genomic landscape (Burbrink and Gehara 2018;Thom et al 2021;Provost et al 2022). As levels of isolation associated with physiographic barriers vary through space and time, so too do rates of selection, gene flow, and divergence (Endler 1977;Aguilée et al 2013;Delmore et al 2018;He et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The South American avifauna is widely known as the richest and most diverse in the world (Stotz et al., 1996 ), and extensive research has been devoted to explaining the mechanisms underlying its outstanding diversity (Burney & Brumfield, 2009 ; Haffer, 1969 ; Harvey et al., 2020 ; Ribas et al., 2012 ; Sick, 1967 ; Silva et al., 2019 ; Smith et al., 2014 ). Comparative analyses of genetic variation in co‐distributed taxa have featured prominently among those studies, and they have generated important insights into the diversification and biogeographical history of the South American biota (Bocalini et al., 2021 ; Carnaval et al., 2009 ; Harvey et al., 2017 ; Johnson et al., 2023 ; Lima‐Rezende et al., 2022 ; Musher et al., 2022 ; Naka & Brumfield, 2018 ; Silva et al., 2019 ; Thom et al., 2021 ; Thom, Xue, et al., 2020 ). However, whereas ample research has focused on the mechanisms generating and maintaining diversity in species‐rich areas, such as the Amazonian and the Andean realms (Carvalho et al., 2021 ; Gergonne et al., 2022 ; Hazzi et al., 2018 ; Miranda et al., 2021 , among others), the mechanisms responsible for the diversity of regions with less homogeneous habitats remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%